Effect of solidification rate on representative impurities distribution in Si-Cu alloy. (1st July 2013) - Fang, M; Lu, C H; Lai, H X; Huang, L Q; Chen, J; Ma, W H; Sheng, Z L; Shen, J N; Li, J T; Luo, X T
<x xml:space="preserve">Abstract</x> The main purpose of this article is to demonstrate that solvent refining in combination with directional solidification can be used for preparation of high purity metallurgical grade silicon for solar cells. Silicon was alloyed with copper and grew under different solidification rates from Si-Cu alloy melt. A detailed analysis of the microstructures and morphologies of Si-Cu alloy has been carried out, focusing on the distribution characteristic of representative impurities affected by solidification rate. The experimental results indicated that copper addition promotes segregation of metal impurities Fe, Al and Ca from metallurgical grade silicon, and the purification effect is more pronounced with the solidification rate decreases. It was also determined that the representative non-metallic impurity phosphorus has a remarkable separation performance after alloying with copper, which can be helpful for the phosphorus removal.